Targeting MicroRNA Function in Acute Pancreatitis - Xiang, Hong; Tao, Xufeng; Xia, Shilin; Qu, Jialin; Song, Huiyi; Liu, Jianjun; Shang, Dong (Frontiers in Physiology, 2017)
Acute pancreatitis (AP) is a common gastrointestinal disorder that featured by acute inflammatory responses leading to systemic inflammatory response syndrome (SIRS) or multiple organ failure. A worldwide increase in annual incidence has been observed during the past decade with high acute hospitalization and mortality. Lack of any specific treatment for AP, even to this day, is a reminder that there is much to be learned about the exact pathogenesis of AP. Fortunately, the discovery of microRNA (miRNA) has started an entirely new thought process regarding the molecular mechanism associated with the disease processes. Given the extensive effort made on miRNA research, certain types of miRNA have been identified across a variety of biological processes, including cell differentiation, apoptosis, metabolism, and inflammatory responses. Mutations in miRNA sequences or deregulation of miRNA expression may contribute to the alteration of a pivotal physiological function leading to AP. Designing miRNA-related tools for AP diagnosis and treatment presents a novel and potential research frontier. In this mini-review, we summarize the current knowledge of various miRNAs closely interacting with AP and the possible development of targeted miRNA therapies in this disease, which may benefit the development of potential disease biomarkers and novel treatment targets for future medical implications.